A250 HNF4A'S NEW ROLE IN DNA REPAIR COULD BE A POTENTIAL THERAPEUTIC TARGET FOR COLORECTAL CANCER TREATMENT. (1st March 2018) - Wilson, S; Babeu, J; Drissi, R; Levesque, D; Boudreau, F; Boisvert, F
Abstract: Background: Colorectal carcinomas typically feature an upregulation of the P2 isoform class of HNF4α. The expression of P2-HNF4α correlates with cell proliferation. Despite this link, the functional role that P2-HNF4α plays in the phenotype of colorectal cancer is poorly understood. Recently, we demonstrated that P2-HNF4α is involved in DNA repair by forming complexes with DNA repair proteins. Drugs specifically targeting DNA repair proteins have become promising avenues for treatment of colorectal cancer as of late. Aims: The goal of our study was to determine whether the newly demonstrated link between P2-HNF4α and DNA repair proteins could potentially be exploited for colorectal cancer treatment. Methods: The complexes of interaction of P2-HNF4α were identified by quantitative proteomics (GFP-Trap and BioID). Immunofluorescence showed HNF4α's colocalization to foci of DNA damage (γH2AX). The efficiency of non-homologous end-joining (NHEJ) was quantified by flow cytometry using a GFP reporter system. Finally, the effect of a PARP inhibitor (olaparib) coupled to knocked down P2-HNF4α expression (shRNA) will be observed. Results: In total, 1066 proteins were identified, by BioID or GFP-Trap, as cofactors of P2-HNF4α. Through BioID, 1007 cofactors of P2-HNF4α were identified in the 293T and HCT116 cell lines, and 59 cofactors were identified in the 293T cell line through GFP-Trap. Many common targets are known to be involved in DNA repair and also cancerous mechanisms. Some common DNA repair targets, p53, PARP1, Rad50, and DNA-PK, were then shown to interact with endogenous P2-HNF4α in HT-29 and LoVo cells. Following genotoxic stress, induced by micro-irradiation or etoposide, immunofluorescence revealed that P2-HNF4α colocalizes to DNA damage loci (γH2AX) in the nucleus of HT-29 and LoVo colorectal cancerous cell lines. Furthermore, we observed a 35% decrease in efficiency of non-homologous end joining in 293 cells where P2-HNF4α was overexpressed. The effect of olaparib on NHEJ and concomitant P2-HNF4α loss will be quantified as well. Conclusions: For the first time, we demonstrated the functional involvement of P2-HNF4α in NHEJ. Furthermore, HNF4α's involvement in DNA repair is a previously undescribed non-transcriptional role for the transcription factor. Studies are currently underway to determine whether this link between P2-HNF4α and DNA repair could be exploitable in the context of colorectal cancer. Funding Agencies: CIHRNSERC